Valuing talent: Do CEOs' ability and discretion unambiguously increase firm performance - Cheung, Kwok Tong Samuel; Naidu, Dharmendra; Navissi, Farshid; Ranjeeni, Kumari (Journal of Corporate Finance, 2017)
This study investigates how the association between more able managers and firm performance, documented in prior research, is affected by the joint effect of managerial discretion and monitoring quality. We find that higher levels of managerial discretion afford more able managers to further improve firm outcomes only when such discretion is monitored closely to curb more able managers' rent seeking incentives. Our results are robust to a battery of additional and sensitivity analyses that we perform.